A comprehensively revised strategy that improves the specific activity and long-term stability of clinically relevant 89Zr-immuno-PET agents. Issue 37 (4th September 2018) - Bhatt, Nikunj B.; Pandya, Darpan N.; Rideout-Danner, Stephanie; Gage, Howard D.; Marini, Frank C.; Wadas, Thaddeus J.
Abstract : Zirconium-89 is currently being used in numerous clinical trials involving monoclonal antibodies and positron emission tomography. A comprehensively revised protocol for the production, quality control and long-term storage of 89 Zr-immuno-PET radiopharmaceuticals. Abstract : Zirconium-89 is currently being used in numerous clinical trials involving monoclonal antibodies and positron emission tomography. This report describes a revised strategy that reduces preparation time while increasing the specific activity of clinically relevant immuno-PET agents. Additionally, it demonstrates that n -acetyl-l -cysteine acts as a superior radioprotective agent that improves long-term stability without compromising antigen affinity in vivo .